A New Micromethod for Evaluating Lymphocyte Responses to Phytohemagglutinin: Quantitative Analysis of the Function of Thymus-Dependent Cells - Park, B. H. (1972)
We have developed a new micromethod for testing phytohemagglutinin stimulation of human lymphocytes. 50 μl of peripheral blood is incubated at 37°C directly, without cell separation, with 50 μl of tissue culture medium containing 50μg of phytohemagglutinin for 24 hr. Then, 0.5 μCi of tritiated thymidine in 50 μl of tissue culture medium is added and incubated for an additional 16 hr. After incubation, erythrocytes are selectively lysed in distilled water, and white blood cells are trapped quickly on a Millipore filter. The radioactivity of the filter is then assessed by a scintillation counter. The requirement of extremely small amounts of blood and a short incubation time are advantages. Further, this method provides a most useful evaluation of thymusdependent cell populations in man and experimental animals and, for the first time, this method provides the possibility of quantitating the deficiency of thymus-dependent cells.